2003
DOI: 10.1073/pnas.1035999100
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 production from activated T cells is required for the spontaneous development of destructive arthritis in mice deficient in IL-1 receptor antagonist

Abstract: IL-17 is a T cell-derived, proinflammatory cytokine that is suspected to be involved in the development of various inflammatory diseases. Although there are elevated levels of IL-17 in synovial fluid of patients with rheumatoid arthritis, the pathogenic role of IL-17 in the development of rheumatoid arthritis remains to be elucidated. In this report, the effects of IL-17 deficiency were examined in IL-1 receptor antagonist-deficient (IL-1Ra ؊/؊ ) mice that spontaneously develop an inflammatory and destructive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
374
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 447 publications
(394 citation statements)
references
References 31 publications
14
374
0
2
Order By: Relevance
“…Il17 –/– mice show significantly reduced severity in various inflammatory and autoimmune disease models, such as collagen‐induced arthritis,6 Il1rn −/− mouse arthritis,7 EAE8 and imiquimod (IMQ)‐induced skin inflammation,9, 10 suggesting critical roles of IL‐17 in inflammatory/autoimmune diseases. γδ 17 cells are detected in inflamed tissues of these disease models.…”
Section: The Pathogenic Roles Of γδ17 Cells In Mouse Inflammatory Dismentioning
confidence: 99%
See 2 more Smart Citations
“…Il17 –/– mice show significantly reduced severity in various inflammatory and autoimmune disease models, such as collagen‐induced arthritis,6 Il1rn −/− mouse arthritis,7 EAE8 and imiquimod (IMQ)‐induced skin inflammation,9, 10 suggesting critical roles of IL‐17 in inflammatory/autoimmune diseases. γδ 17 cells are detected in inflamed tissues of these disease models.…”
Section: The Pathogenic Roles Of γδ17 Cells In Mouse Inflammatory Dismentioning
confidence: 99%
“…As described, the importance of IL‐17 in the development of rheumatoid arthritis (RA) is suggested in mouse models and γδ 17 cells are accumulated in arthritic joints,7, 20, 22, 24 but the importance of γδ 17 cells in patients with RA is controversial. A recent report shows that V δ 2 + γδ T cells accumulate in the synovium of patients with RA and produce high levels of IL‐17 as well as IFN‐ γ 98.…”
Section: γδ17 Cells In Human Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying T cells that initiate acute uveitis or mechanisms that allow autoreactive T cells to persist in the retina and mediate recurrent uveitis is a challenge. Interleukin-17-producing T (Th17) cells produce TNF-a, IL-21, IL-22, granzyme B, contribute to host defense against microbial agents and have recently been implicated in the development of chronic inflammation in several mouse models [3][4][5], suggesting that the Th17 subset may also be involved in the pathogenesis of immune-mediated diseases in humans, including uveitis. Several studies have reported that IL-23 and IL-17 are elevated in Behc -et's and VKH patients with active uveitis [6][7][8][9], while elevated serum levels of IL-23 and Th17-induced cytokines were found to correlate with intraocular inflammation after cataract surgery in VKH patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…Judging from these findings, GPI-induced arthritis is considered a useful murine model for analyzing the role of CD4ϩ T cells in the effector phase of the arthritis. Several studies have examined the roles of Th17 cells, a distinct lineage of CD4ϩ effector T cells, in various arthritis models (14)(15)(16)(17). CIA was shown to be partially suppressed in IL-17-deficient mice (16), whereas it was exacerbated in IFN␥-deficient mice or IFN␥ receptor-deficient mice (18)(19)(20).…”
mentioning
confidence: 99%